Sleep Disturbance Among Older Korean Immigrants. (17th December 2021) - Song, Yeonsu; Kim, Haesook; Lee, Diane; Ryan, Gery; Kramer, B Josea; Martin, Jennifer; Hays, Ron; Choi, Sarah
Abstract: Little is known about sleep disturbance among older Korean immigrants living in the United States. In this exploratory study, we conducted focus groups with 6 and phone interviews with 22 older Korean immigrants to explore and understand their sleep experiences. Three members of the research team fluent in Korean independently coded each focus group and phone interview transcript to identify underlying themes. The following themes emerged: Daytime naps were acceptable behaviors, particularly among those who were retired or not employed. Many reported worry and anxiety rumination behaviors that interfered with their sleep. In addition, praying, reading the bible, and singing hymns often occurred while in bed, and smartphone or tablet use was a frequent activity as well. Drinking alcohol and taking sleeping pills were used as a last resort to help with sleep, particularly among those who lived alone. Internal (e.g., biological urge, snoring, medical conditions) and external distractions (e.g., noise) contributed to nighttime awakenings. Living alone and worrying about the future made it difficult for some to return to sleep after awakening. Seeking advice from peers was a common behavior but did not seem to help with sleep. Calming activities such as reading a book, taking a shower, watch television, or writing a diary were routinely performed before bedtime. These findings are consistent with unhealthy sleep behaviors shown in other racial/ethnic minority older adults with poor sleep. Sleep education programs in Korean-speaking churches may be used to target those who are socially isolated and may benefit older Korean immigrants.